Novel waterproof bituminous coating using self-healing microcapsules containing ultraviolet light curing agent. (25th April 2022) - Yang, Peng; Gao, Xu; Wang, Sai; Su, Jun-Feng; Wang, Li-Qing
Graphical abstract: Photographs of bitumen samples with a self-healing process, (a1 ) original state of two bitumen samples without microcapsules, 1 cm long scratch with 0.5 cm deep in each sample, (a2 ) two bitumen samples without microcapsules after a 48h self-healing process under 20 °C with a 1 W/m 2 UV radiation, (b1 -b5 ) the upside bitumen sample without microcapsules in a black mold, the downside bitumen sample with 3.0 wt% microcapsules in a red mold, 1 cm long scratch with 0.5 cm deep in each sample, each sample self-healing under 20 °C for (b1 ) 0h, (b2 ) 12h, (b3 ) 24h, (b4 ) 36h, and (b5 ) 48h. Highlights: Self-healing microcapsules containing ultraviolet light curing agent were successfully fabricated. Microcapsules keep the core material safe in bitumen coating. Microcapsules can complete a self-healing process under the ultraviolet light. Abstract: Bituminous material is widely used in construction and building field, which often need excellent waterproof performance in the process of application. The aim of this work was to design a novel waterproof bituminous coating using self-healing microcapsules containing ultraviolet light curing agent. Core material of microcapsules was a compound of polyurethane acrylate (prepolymer 95 wt%) and 2-hydroxy-2-methyl-phenylacetone (initiator, 5 wt%). Morphology and chemical analysis showed that the cross-linked cured methylether-melamine–formaldehyde (HMMM) shell material protected core material under the condition of high temperature molding and avoid sunlight. The microcapsules had perfect spherical shape with a mean size of 20 μm and shell thickness of 2 μm. Microcapsules dispersed in bitumen homogeneously without agglomeration. No deboning was found in the interface between microcapsules and bitumen. Microcapsules resisted the temperature above 200 °C and remained the core material safety in shells. Through a man-made microcrack experiment, it proved that the bitumen sample with 3.0 wt% microcapsules completed a quick self-healing process with the help of ultraviolet light. Waterproof measurement also indicated that the microcrack in bituminous coating disappeared with the help of self-healing microcapsules under ultraviolet light. In other words, the rapid disappearance of microcracks can contribute to improving the waterproof performance of bituminous coating.